Sundanese Ethnomathematics Context in Primary School Learning - Nugraha, Trisna; Maulana, M.; Mutiasih, Palupi (Universitas Pendidikan Indonesia, 2020)
Mathematics is mostly related to human life, thus, humans are required to have the mathematical understanding ability in solving life problems since in the elementary school age. Therefore, mathematics learning at school should have relevance value to construct mathematical concept that can be used in real life. Innovative mathematics learning through Contextual Learning (CTL) model based on Sundanese Culture Ethnomathematics as a local wisdom at which humans use mathematics in their real life, was chosen as a deep solution to increase the mathematical understanding ability, because students live in their culture and society. This study employsan experimental method by conducting pretest and postest control group design. The purpose of this study is to determine the increasing of students’ mathematical understanding ability on experiment class (using CTL model based on Sundanese Ethnomathematics) and control class (using conventional learning model). The result of this study produced conclusion that CTL based on Sundanese ethnomahtematics and conventional model can increasethe mathematical understanding ability significantly. However, the application of CTL model based on Sundanese Ethnomathematics was significantly better than conventional model (62.29%) to increase students’ mathematical understanding ability on learning the basic concepts of rectangular geometry for 4th grade students of elementary school.